2000
DOI: 10.1111/j.1469-7793.2000.t01-1-00063.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of ClC‐3 in volume‐activated chloride currents and volume regulation in bovine epithelial cells demonstrated by antisense inhibition

Abstract: A chloride current with mild outward rectification was induced in the native bovine non‐pigmented ciliary epithelial (NPCE) cells by a 23 % hypotonic solution. The current showed no or little inactivation at depolarized steps. ATP blocked 88 and 61 % of the outward and inward components of the volume‐activated chloride current (ICl,vol) with an IC50 of 5.3 and 9.6 mM, respectively. The volume‐activated chloride current was decreased and the activation of the current was delayed by inhibiting endogenous ClC‐3 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 37 publications
6
75
1
Order By: Relevance
“…Generally, hyposmotic shock can result in cell swelling (Stutzin and Hoffmann, 2006). Meanwhile, ClC-3, a member of the CLC family, has been reported to be activated by cell swelling (Duan et al, 1997;Duan et al, 1999), and several studies have suggested that ClC-3 represents a major molecular entity responsible for native volume sensing in outwardly rectifying anion channels of various cell types in hyposmotic media (Wang et al, 2000;Duan et al, 2001;Hermoso et al, 2002).…”
Section: CLmentioning
confidence: 99%
“…Generally, hyposmotic shock can result in cell swelling (Stutzin and Hoffmann, 2006). Meanwhile, ClC-3, a member of the CLC family, has been reported to be activated by cell swelling (Duan et al, 1997;Duan et al, 1999), and several studies have suggested that ClC-3 represents a major molecular entity responsible for native volume sensing in outwardly rectifying anion channels of various cell types in hyposmotic media (Wang et al, 2000;Duan et al, 2001;Hermoso et al, 2002).…”
Section: CLmentioning
confidence: 99%
“…The whole-cell membrane current of a single cell was amplified through an EPC-9 amplifier (HEKA Elektronik Dr. Schulze GmbH, Lambrecht, Germany), and via filtering by 2.9 kHz, the currents were recorded to the Pulse and Pulsefit software system (HEKA Elektronik Dr. Schulze GmbH). Whole-cell patch clamp recording parameters were as follows (11,17): Under the voltage clamp mode, the cells were clamped at 0, ±40 and ±80 mV. Each clamp pulse was held for 200 msec with an interval gap of 4 sec.…”
Section: Determination Of Intracellular Chloride Ion Concentrationmentioning
confidence: 99%
“…In fact, studies have shown that numerous ion channels [such as Ca 2+ channels (8) and K + channels (9)] have a role in osteogenic differentiation. ClC-3 is a subtype of the volume-sensitive chloride channel family that has a role in cell volume regulation (10)(11)(12), as well as in cell proliferation (13), apoptosis (10), cell cycle progression (14) and intracellular acidification regulation in the osteoclast (15). Studies have also reported the involvement of chloride channels in the metabolism of osteoblasts, for example, ClC-3 protein expression can promote osteogenesis via Runx2 gene expression in mouse osteoblasts (16).…”
Section: Introductionmentioning
confidence: 99%
“…ClC-3 was expressed in CNE-2Z cells and has been proposed by others and us to be the molecular candidate involved in the activation or regulation of volume-sensitive Cl Ϫ currents (7,9,18,28,31). To investigate the role of ClC-3 in the activation of the acid-activated chloride currents, the effect of knockdown of ClC-3 expression by ClC-3 siRNA was tested.…”
Section: Suppression Of Clc-3 Protein Expression and Depletion Of Acimentioning
confidence: 99%
“…Analysis of current properties indicates that there are some similarities between the acid-induced Cl Ϫ current and the volume-sensitive Cl Ϫ current. ClC-3 has been proposed by others and us to be the molecular candidate involved in the activation or regulation of volume-sensitive Cl Ϫ current (7,9,18,28). The role of ClC-3 proteins in activation of acidinduced Cl Ϫ current is not clear.…”
mentioning
confidence: 99%